The recent evolution of the natural rate of unemployment - Mary C. Daly; Bart Hobijn; Rob Valletta (Institute for the Study of Labor (IZA), 2011)
The U.S. economy is recovering from the financial crisis and ensuing deep recession, but the unemployment rate has remained stubbornly high. Some have argued that the persistent elevation of unemployment relative to historical norms reflects the fact that the shocks that hit the economy were especially disruptive to labor markets and likely to have long lasting effects. If such structural factors are at work they would result in a higher underlying natural or nonaccelerating inflation rate of unemployment, implying that conventional monetary and fiscal policy should not be used in an attempt to return unemployment to its pre-recession levels. We investigate the hypothesis that the natural rate of unemployment has increased since the recession began, and if so, whether the underlying causes are transitory or persistent. We begin by reviewing a standard search and matching model of unemployment, which shows that two curves - the Beveridge curve (BC) and the Job Creation curve (JCC) - determine equilibrium unemployment. Using this framework, our joint theoretical and empirical exercise suggests that the natural rate of unemployment has in fact risen over the past several years, by an amount ranging from 0.6 to 1.9 percentage points. This increase implies a current natural rate in the range of 5.6 to 6.9 percent, with our preferred estimate at 6.25 percent. After examining evidence regarding the effects of labor market mismatch, extended unemployment benefits, and productivity growth, we conclude that only a small fraction of the recent increase in the natural rate is likely to persist beyond a five-year forecast horizon.
urn:nbn:de:101:1-201107133453
Keywords: E24; J3; J6; 330; equilibrium unemployment; Beveridge curve; structural unemployment; mismatch